Kilka uwag na tle kompensacyjnej funkcji prawa karnego - Pływaczewski, Emil W.; Guzik-Makaruk, Ewa M. (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article is divided into four parts, presenting a restitutive function, from a historical perspective, of compensation in the view of the Criminal Code of 1997, as well as in the view of the Act of 7 July 2005 on State compensation granted to victims of certain prohibited acts. The authors also attempt to summarize and evaluate the amendment. The article is dedicated to the Esteemed Professor Tomasz Kaczmarek, celebrating His jubilee, an Educator of generations of lawyers, an Outstanding representative of the science, whose wide activity and plenteous achievements in various fields indicate great versatility of His interests.
Keywords: funkcje prawa karnego; przepadek i środki odszkodowawcze; ofiara przestępstwa